Heat stress affects dairy cow performance via oxidative stress, hypothalamic–pituitary–adrenal axis, gut microbiota, and multi-dimensional mitigation - Zhang, Qiang; Yang, Lulu; Li, Yunhan; Gu, Pengbo; Si, Riguleng; Zhu, Lin; Zhang, Wenguang (Frontiers in Veterinary Science, 2025)
Against the backdrop of global warming, heat stress has become one of the greatest challenges facing the dairy industry. This review systematically summarizes the multi-dimensional impacts of heat stress on dairy cows and corresponding mitigation strategies under global warming. It covers the evaluation indicators (temperature-humidity index, physiological and behavioral indicators) and classification of heat stress. It analyzes the negative effects on dairy cows’ reproductive performance (e.g., oocyte and sperm damage, hormonal disorders, impaired fetal development) and production performance (e.g., reduced milk yield, deteriorated milk composition). These effects are mediated by physiological mechanisms such as oxidative stress imbalance, hypothalamic–pituitary–adrenal axis (HPA axis) activation, cellular structural damage, altered gene expression, and disrupted host-gut microbiota interactions. Additionally, the review integrates interdisciplinary mitigation strategies including environmental optimization, nutritional regulation, genetic breeding, and intelligent monitoring. It provides theoretical and practical references for constructing a sustainable heat stress prevention and control system.